DNA fragmentation, an indicator of apoptosis, in cultured black tiger shrimp penaeus monodon infected with white spot syndrome virus (WSSV) - Sahtout, A.H.; Hassan, M.D.; Shariff, M. (Inter-Research, 2001)
Fifty black tiger shrimp Penaeus monodon from commercial cultivation ponds in Malaysia were examined by Tdt-mediated dUTP nick-end labeling (TUNEL) fluorescence assay and agarose gel electrophoresis of DNA extracts for evidence of DNA fragmentation as an indicator of apoptosis. From these specimens, 30 were grossly normal and 20 showed gross signs of white spot syndrome virus (WSSV) infection. Of the 30 grossly normal shrimp, 5 specimens were found to be positive for WSSV infection by normal histology and by nested polymerase chain reaction (PCR) analysis. All of the specimens showing gross signs of WSSV infection were positive for WSSV by normal histology, while 5 were positive by nested PCR only (indicating light infections) and 15 were positive by 1-step PCR (indicating heavy infections). Typical histological signs of WSSV infection included nuclear hypertrophy, chromatin condensation and margination. None of the 25 grossly normal shrimp negative for WSSV by 1-step PCR showed any signs of DNA fragmentation by TUNEL assay or agarose gel electrophoresis of DNA extracts. The 10 specimens that gave PCR-positive results for WSSV by nested PCR only (i.e., 5 grossly normal shrimp and 5 grossly positive for WSSV) gave mean counts of 16 ± 8% TUNEL-positive cells, while the 25 specimens PCR positive by 1-step PCR gave mean counts of 40 ± 7% TUNEL-positive cells. Thus, the number of TUNEL positive cells present in tissues increased with increasing severity of infection, as determined by gross signs of white spots on the cuticle, the number of intranuclear inclusions in histological sections, and results from single and nested PCR assays. DNA extracts of PCR-positive specimens tested by agarose gel electrophoresis showed indications of DNA fragmentation either as smears or as 200 bp ladders. Given that DNA fragmentation is generally considered to be a hallmark of apoptosis, the results suggested that apoptosis might be implicated in shrimp death caused by WSSV.